A great deal of ruin : financial crises since 1929 - Gerber, James (Cambridge : Cambridge University Press, 2019)
A Great Deal of Ruin provides an accessible introduction to the enduring problem of financial crises. Illustrated with historical analysis, case studies, and clear economic concepts, this book explains in three parts what financial crises are, how they are caused and what we can learn from them. It begins with a taxonomy of crises and a list of factors that increase the risk for countries experiencing a financial crisis. It then examines five of the most important crises in modern economic history, beginning with the Great Depression and ending with the subprime crisis in the United States and its evolution into a debt crisis in the Eurozone. The book concludes with a set of lessons that can be learnt from the crises of the past. It will appeal to university students as well as general readers who are curious to learn more about the recent subprime crisis and other financial crises.
Title from publisher's bibliographic system (viewed on 09 Aug 2019).
Keywords: Financial crises -- History; Banks and banking -- History; Corporations -- Finance -- History